Iron Extraction from Coal Fly Ash Using HCl Solution - Setyo, Slamet Budi; Sulistyaningsih, Triastuti; Prasetya, Agung Tri; Kusumastuti, Ella (Universitas Negeri Semarang, 2021)
About 780 million tonnes of fly ash are produced annually worldwide. The use of fly ash is still minimal, causing fly ash piles to increase. Based on this, a study was conducted on the extraction of iron from coal fly ash using HCl as a solvent. This study aims to determine the Fe content in fly ash extracted using HCl with variations in HCl concentration and extraction time. This research begins with the preparation of fly ash samples using an oven. Fly ash that has been prepared and extracted using HCl added with MIBK and EDTA was then characterized using XRF, FTIR and AAS. The results showed that the highest Fe content (11.48%) was obtained from the extraction using 9N HCl for 1 minute. The greater the concentration of HCl and the faster the extraction time, the more Fe extracted.